2022
DOI: 10.37116/revistaenergia.v19.n1.2022.520
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel inverter D-STATCOM for reducing total harmonic distortion in a non-linear loads electrical distribution system

Abstract: El paper presenta el análisis de rendimiento de un Inversor Multinivel en Cascada D-STATCOM para reducir la distorsión armónica total, que basa su control en la estrategia del marco de referencia síncrono.                                                 La distorsión armónica es recurrente en las redes de distribución eléctrica actuales debido a la presencia de cargas no lineal, como electrodomésticos u otros dispositivos que tengan en sus componentes electrónica de potencia. El funcionamiento del … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The academic literature has addressed the integration of IoT devices into the electrical network from various perspectives. For instance, it has been demonstrated that a multilevel inverter D-STATCOM can reduce total harmonic distortion in electrical-distribution systems with nonlinear loads [39]. This type of device exemplifies the application of advanced technology to improve power quality in the electrical network.…”
Section: Power-system Automation In Electrical Networkmentioning
confidence: 99%
“…The academic literature has addressed the integration of IoT devices into the electrical network from various perspectives. For instance, it has been demonstrated that a multilevel inverter D-STATCOM can reduce total harmonic distortion in electrical-distribution systems with nonlinear loads [39]. This type of device exemplifies the application of advanced technology to improve power quality in the electrical network.…”
Section: Power-system Automation In Electrical Networkmentioning
confidence: 99%